Dietary Predictors of Maternal Prenatal Blood Mercury Levels in the ALSPAC Birth Cohort Study...Avon Longitudinal Study of Parents and Children - Golding, Jean; Steer, Colin D.; Hibbeln, Joseph R.; Emmett, Pauline M.; Lowery, Tony; Jones, Robert (Environmental Health Perspectives, 2013)
Background: Very high levels of prenatal maternal mercury have adverse effects on the developing fetal brain. It has been suggested that all possible sources of mercury should be avoided. However, although seafood is a known source of mercury, little is known about other dietary components that contribute to the overall levels of blood mercury. Objective: Our goal was to quantify the contribution of components of maternal diet to prenatal blood mercury level. Methods: Whole blood samples and information on diet and sociodemographic factors were collected from pregnant women (n = 4,484) enrolled in the Avon Longitudinal Study of Parents and Children (ALSPAC). The blood samples were assayed for total mercury using inductively coupled plasma dynamic reaction cell mass spectrometry. Linear regression was used to estimate the relative contributions of 103 dietary variables and 6 sociodemographic characteristics to whole blood total mercury levels (TBM; untransformed and log-transformed) based on R2 values. Results: We estimated that maternal diet accounted for 19.8% of the total variation in ln-TBM, with 44% of diet-associated variability (8.75% of the total variation) associated with seafood consumption (white fish, oily fish, and shellfish). Other dietary components positively associated with TBM included wine and herbal teas, and components with significant negative associations included white bread, meat pies or pasties, and french fries. Conclusions: Although seafood is a source of dietary mercury, seafood appeared to explain a relatively small proportion of the variation in TBM in our UK study population. Our findings require confirmation, but suggest that limiting seafood intake during pregnancy may have a limited impact on prenatal blood mercury levels.